Submandibular gland pleomorphic adenoma masquerading as a multinodular goitre: a case report - Chaudhary, Hardik M.; Sathwara, Kunal G.; Prajapati, Ankit M.; Adhyaru, Chirag D.; Bumatariya, Divyesh J. (International Surgery Journal, 2024)
Tumors of the salivary gland comprise of a small percentage of all head and neck tumors, of which nearly 80% are benign. The submandibular gland tumors constitute only 5-10% of this group, of which pleomorphic adenoma is the commonest type. They can weigh several kilograms and grow to ludicrous sizes. If left untreated, they may result in facial deformity and airway compromise. We describe a case of a big pleomorphic adenoma arising from submandibular salivary gland that developed in a 65 years old female presenting as a swelling in right side of neck since 15 years. The dimensions of the lesion were roughly around 8×12×11 cm. During surgical examination, a solid mass that originated from the right submandibular gland was discovered to be linked to both the skin and the soft tissue beneath it. Pleomorphic adenoma was confirmed by histopathological examination. Review and discussion of the relevant literature was conducted. This article’s emphasis is on the fact that, although the pleomorphic adenoma is a well-reported entity, they can attain very large sizes involving the neck region and can misrepresent itself leading to diagnostic dilemma due to many possible differential diagnoses of neck swellings.